Adding Kalman filter into ESI: an anomaly detection approach for middleware metadata - Corbisier, Leonardo Leal (2022)
Internship Report presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence